Development of a Laboratory Equipment Pocketbook on Organ and Organ System Materials for Grade XI Senior High School Students - Rani Sukrianis; Darmadi Darmadi; Diah Anugrah Dipuja (Journal of Education and Learning Research, 2026)
Biology learning in senior high school is important for understanding life concepts and biological processes. However, organ and organ system materials are often considered difficult because they involve broad concepts, scientific terminology, and laboratory practical activities. This study aimed to develop a laboratory equipment pocketbook for Grade XI senior high school students on organ and organ system materials, integrating laboratory equipment identification with QR codes linked to learning videos. The novelty of the pocketbook lies in integrating laboratory equipment identification with organ and organ system materials and QR codes linked to learning videos, providing a resource for learning support. The research employed the Research and Development (R&D) method using the ADDIE model, limited to the development stage. The study was conducted from December 2025 to February 2026 involving expert validators, Biology Education students, and Grade XI students. Data were collected through observations, interviews, validation sheets, and response questionnaires using a four-point Likert scale. Validation results showed an average score of 3.70, categorized as “very valid.” Limited trial stages I and II obtained average scores of 3.83 and 3.92, respectively, both categorized as “very good.” The findings indicate that the pocketbook is feasible and well-received as a supporting resource for introducing laboratory equipment in biology learning.